Meningkatkan Keterampilan Membaca Awal Melalui Media Pembelajaran Flashcard pada Anak Usia 5-6 Tahun - Sopiah, Sopiah; Irwansyah, Asep; Riza, Eva; Puspitasari, Putri Ratih; Suryani, Nani (Jurnal Inovasi Pendidikan MH Thamrin, 2022)
The development of reading skills needs to be stimulated from an early age through various media, starting with symbols. The media used must be able to stimulate children's interest in reading. The results of observations that have been made in Kindergarten/ Raudhatul Athfal (RA) Al Falah Bogor, there is a low initial reading ability, which is characterized by the low ability of children to recognize letter symbols, syllables, and words. Most children cannot read their own names yet. The learning method used by the teacher has not varied, it is done conventionally, namely through writing written by the teacher on the blackboard. The purpose of this study was to improve early childhood reading skills through flashcard media in RA. Al-Falah Bogor. The methodology in this study is Classroom Action Research which is qualitative with data collection techniques carried out through observation, interviews, or interview and documentation to obtain the necessary data. shows an increase in the ability to read beginners who can achieve success criteria, namely the acquisition of an average percentage of more than 75%. In the Pre-Action stage, children's initial reading ability obtained an average percentage of 36.09% with poor criteria and increased to 52.30% with moderate criteria in Cycle I, and to 79.86% with high criteria in Cycle II. Results of this study indicate that flashcard media can improve beginner reading skills.